Laboratory efficacy of mycoparasitic fungi (Aspergillus tubingensis and Trichoderma harzianum) against tropical bed bugs (Cimex hemipterus) (Hemiptera: Cimicidae) - Zahran, Zulaikha; Mohamed Nor, Nik Mohd Izham; Dieng, Hamady; Satho, Tomomitsu; Ab Majid, Abdul Hafiz (Elsevier, 2017)
Objective: To test the effectiveness of conidial spore formulations [Aspergillus tubingensis (A. tubingensis) and Trichoderma harzianum (T. harzianum)] against tropical bed bugs, Cimex hemipterus. Methods: Spore formulations were made from two fungal strains, T. harzianum and A. tubingensis. The bed bugs were exposed to the conidial spores placed soaked onto a fabric cloth for 1 h and the mortality counts were recorded daily until 14 days. Results: Mean survival times based on Kaplan–Meier survival analysis showed no significant differences between all the concentrations in both the fungal isolates: T. harzianum and A. tubingensis. However, the evaluation of both the isolates in terms of virulence resulted in low lethal hours in all the concentrations except for the high concentration of A. tubingensis (LT50 = 44.629 h) at the conidial exposure of 1 × 106 spores/ mL. Rapid mortality of the bed bugs was observed from Day 6 to Day 12, ranging from 13% to 90% in all three concentrations of A. tubingensis. With reference to the T. harzianum exposure, the concentration of 1 × 104 spores/mL displayed a gradual increase in the percentage mortality of 90 on Day 14. Conclusions: Approaches to the bed bugs treatment should be explored in-depth using a natural biological agent like fungus especially A. tubingensis to reduce this pest population, in order to replace chemical methods.